Acute Fatal Gastric Dilatation and Volvulus in a Captive Adult Linnaeus’s Two-Toed Sloth (Choloepus didactylus) in Amazon Biome - Hanna Gabriela da Silva Oliveira; Cinthia Távora de Albuquerque Lopes; Letícia Yasmin Silva Correa; Roberta Martins Crivelaro Thiesen; Rodrigo Otavio Silveira Silva; Francisco Alejandro Uzal; Sheyla Farhayldes Souza Domingues; Felipe Masiero Salvarani (Animals)
This study aims to report the dietary and daily management, clinical signs, complementary exams, and pathological findings related to an acute and fatal case of gastric dilatation and volvulus (GDV) in a captive Linnaeus’s two-toed sloth (Choloepus didactylus) in the Amazon Biome. An adult female sloth, rescued after being electrocuted, was housed at the Wildlife Section of the Veterinary Hospital (WSVH) of the Institute of Veterinary Medicine (IVM) at the Universidade Federal do Pará (UFPA). It was fed a diverse diet that included animal protein, fruits, vegetables, and greens, with vitamin and mineral supplementation. After five years, the sloth was found in its enclosure hyporesponsive, dehydrated, hypothermic, and hyperventilating, with an abdominal dilation of firm consistency. During emergency care, the animal died. Fecal samples collected two days before death were positive only for Clostridium perfringens type A. Necropsy findings included dilatation of the squamous gastric compartment due to gas accumulation, with necrotic and hemorrhagic mucosa, a 180–270° volvulus obstructing the gastroesophageal region, and intestinal mucosal hyperemia. Histopathology revealed marked congestion with hemorrhage and gastric mucosal necrosis, along with tertiary lymphoid follicles in the submucosa. To the authors’ knowledge, this is the first report of GDV in a sloth in Brazil. Further research is needed to develop appropriate approaches to GDV in captive sloths.